Managerial Efficiency and Corporate Leverage Policy in Pakistan - Qamar uz Zaman; M. Kabir Hassan; Hafiz Muhammad Arshad; Sahar Sultan; Ayesha Ashraf (Asian Academy of Management Journal of Accounting and Finance, 2020)
This study aims to observe the relationship between managerial efficiency (ME) and corporate leverage policy. We use data from Pakistani listed firms from 1999 to 2018. In our stepwise methodology, initially, we used data envelopment analysis (DEA) to acquire firm total efficiency (FTE) scores and then Tobit regression to acquire residual values. These residual values are used as a proxy of ME. After employing various definitions of leverage and fixed effect regression technique, the study observes that ME has a positive and significant relationship with leverage. It indicates that efficient managers are more inclined towards debt financing. It also implies that restraining managerial discretion through debt financing may also make them efficient. Therefore, finding partially approves the agency perspective in the case of Pakistan. Overall, this study offers theoretical contributions to better understand the role of ME and leverage, and the use of DEA approach. Further, this study is fundamental to observe the ME and leverage concerning agency theory in general, and specifically in the context of Pakistan.